Seni Grafis Yogyakarta dalam Wacana Seni Kontemporer - Wiwik Sri Wulandari (Journal of Visual Art and Design, 2008)
The Indonesian visual art movement are through hard time, struggling in response to the ever happen complexity of art in the world around; as experience by Yogyakarta's print making. Thus, it is interesting to know how it survive and contribute to the Indonesian visual art. The presented paper focuses on understanding the movement of Yogyakarta's printmaking in relation to the discouse of Indonesian contemporary art through visual and conceptual analysis. Results show that visual expressions of the Yogyakarta's printmaking has visually and conceptually evolved following the latest development in the contemporary art discourse.